Eksekusi Jaminan Pada Pembiayaan Mudharabah Karena Force Majeur Ditinjau Dari Fatwa Dewan Syariah Nasional NO :07 DSN-MUI/IV/2000: Studi Kasus BSI Kecamatan Padang BolakKabupaten Padang Lawas Utara - Rahma Dewi Siregar; Mustapa Khamal Rokan; Annisa Sativa (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
BSI Kcp. Gunungtua carries out its business activities based on sharia principles. One of its business activities is mudharabah financing. In the implementation and resolution of mudharabah financing, there are still problems, practice in the field is still far from what is stated by the DSN-MUI fatwa. BSI Kcp. Gunung Tua has not really implemented the DSN-MUI Fatwa in its entirety, so that business actors receive capital financing from BSI Kcp. Gunung Tua is still obliged to return the capital in full, even if the capital manager (mudharib) experiences an accident or event beyond the management's fault (Overmacht). This research aims to determine (1) The concept of customer responsibility in mudharabah financing caused by Force Majeure based on the Fatwa of the National Sharia Council No: 07 DSN-MUI/IV/2000, (2) Implementation of collateral execution in mudharabah financing due to Force Majeure at BSI Kcp.Gunung Tua and (3) Is execution of collateral in mudharabah financing permitted due to force majeure based on National Sharia Council Fatwa No: 07 DSN-MUI /IV/2000. Mudharabah financing is permitted as long as it does not conflict with sharia principles. If a sharia financial institution uses a Mudharabah contract, the sharia financial institution must follow the provisions of the DSN Fatwa. The DSN Fatwa regarding mudharabah financing is DSNMUI Fatwa No.07/DSN-MUI/IV/2000. The research method used is a descriptive method, namely describing the implementation of collateral execution. in mudharabah financing, the primary data source is the manager of BSI Kcp.Gunung Tua, the research technique used is interviews. The results of this research can be concluded that (1) The concept of customer responsibility for mudharabah financing implemented at BSI Kcp. Gunung Tua is that customers must fulfill their obligations to make payments unless it is caused by an unintentional error (Force Majeure), (2) Execution of guarantees in mudharabah financing due to Force Majeure at BSI Kcp. Gunung Tua and (3) Is the execution of guarantees in mudharabah financing permitted due to force majeure based on National Sharia Council Fatwa No: 07 DSN-MUI /IV/2000.